Editorial - Poudel, Kamal Kumar (Education and Development, 2025)
Editorial Education and Development is one of the two journals published by Tribhuvan University's Research Centre for Educational Innovation and Development (CERID). In harmony with the functioning of CERID, the journal centrally covers education. More specifically, the priority areas of the journal include higher education, education policy, alternative education, curriculum, classroom teaching, teaching methodology, pedagogy and critical pedagogy, learning, technology and its educational application, current issues in education, and innovation in education/pedagogy. The articles published in this (34th) volume are, accordingly, around these very themes. The articles in this volume are nine of the accepted manuscripts out of the seventeen which were submitted for publication in this issue. The articles published in this issue cover varied areas, chiefly, language education, mathematics education, and curriculum – some of them in integration with technology. The articles have come to the form they are in after a thorough and rigorous process of the double-blind peer review process followed by the editors’ meticulous revision on the academic as well as linguistic aspects. Yet, comments and suggestions from the scholarly readers are always wholeheartedly welcome. The publication, as an outcome, is the result of common efforts of a network of contributors. Typically, we are grateful to the researchers-authors who are, in fact, both the body and the soul of the journal. In reality, the journal exists with their contribution. We hope and believe that the researchers-authors will continually support us by contributing to our effort of disseminating research-based knowledge to a wider readership through the journal in the future, too. Chief Editor Prof. Kamal Kumar Poudel, HD 6/14/2025